1981
DOI: 10.1007/bf00271208
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of bacteriophage T4 tail fibers: Identification and characterization of the nonstructural protein gp57

Abstract: Formation of both the tail fiber and the baseplate of bacteriophage T4 depends on the product of T4 gene 57. A single amber mutation in that gene causes loss of two T4-specific proteins. Their molecular weights are 18,000 and about 6,000, respectively, based on their electrophoretic mobilities in SDS-polyacrylamide gels. E. coli carrying a cloned T4 DNA fragment of about 700 basepairs, which directs the synthesis of the smaller protein only, specifically supports the growth of gene 57 amber mutants. We conclud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

1982
1982
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Their coding sequences start at position 105 and 123, respectively, but both terminate at position 285 using the same reading frame. Their molecular weights agree well with the molecular weight of the single polypeptide (about 6000 daltons), that is synthesized in vivo in E. coli under direction of the cloned T4 DNA fragment (3). The direction of protein synthesis for the supposed gp57A is in accordance with the direction of transcription of that region in T4 infected E. coli (13).…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Their coding sequences start at position 105 and 123, respectively, but both terminate at position 285 using the same reading frame. Their molecular weights agree well with the molecular weight of the single polypeptide (about 6000 daltons), that is synthesized in vivo in E. coli under direction of the cloned T4 DNA fragment (3). The direction of protein synthesis for the supposed gp57A is in accordance with the direction of transcription of that region in T4 infected E. coli (13).…”
Section: Discussionsupporting
confidence: 66%
“…Final proof for the identity of gp57A can only be derived from amino acid analysis of the N-terminus of that protein. Cloning experiments have shown that gene 57 is expressed independently of its orientation in the phage fd vector (3). This suggests that the signal sequences for transcription (16) and translation (17,18) are contained in the cloned T4 DNA fragment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chaperone P57A participates in the assembly of P34 and P37 and also in the assembly of the short TF, P12 (15,19). P38 is necessary (in addition to P57A) for the trimerization of gp37 to form the mature P37 rod, which initiates the extension of LTF assembly (9, 13).…”
mentioning
confidence: 99%